Metode Struktur Analitik Sintetik (SAS): Pengaruh Bahasa Arab Siswa terhadap Kemampuan Menulis - Qowiyah, Nauroh; Akbar, Doni Wahidul (Ta'limi | Journal of Arabic Education and Arabic Studies, 2025)
One of the most crucial language abilities is writing. Nonetheless, a lot of students still struggle with writing in Arabic, particularly when it comes to word or phrase construction. This challenge is frequently brought on by language gaps, a lack of knowledge of writing conventions, and structural discrepancies between Arabic and Indonesian. The Structure Analytic Synthetic (SAS) approach is seen to be a good way to get better at writing. The purpose of this study is to ascertain how the SAS approach has affected the writing abilities of seventh-grade students at SMP Muhammadiyah 35 Jakarta. This study employs a pre-experimental design and a quantitative methodology. 16 pupils from class VII 1 are the study's subjects. Written tests were used to collect data both before and after the treatment (pre-test and post-test). The study's findings demonstrate that when the SAS approach was used, pupils' writing abilities significantly improved. Compared to the average pre-test score of 65.81, the average post-test score is higher at 86.43. The significance threshold of 0.05 is exceeded by the paired sample t-test's significance value of 0.001. The SAS approach has been shown to be successful in improving pupils' Arabic writing abilities. Arabic language instructors can use the study's findings as a guide for choosing efficient teaching strategies to help their students become better writers.